Evaluation of antioxidant potential of melatonin in periodontitis with a focus on vitamin C - Marawar, Anagha P.; Marawar, Pramod P.; Nandal, D. H.; Kunkulol, Rahul R. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The present study was done with an objective to evaluate the effect of melatonin as an antioxidant, with a focus on vitamin C, in patients suffering from periodontitis. Methods: This study was conducted jointly in the Department of Periodontics, Rural Dental College, and Department of Pharmacology, PIMS, Loni. Patients suffering from chronic periodontitis, of age between 18 to 65 years of either gender were included in the study, after obtaining a written informed consent. Patients were divided into three Groups. Group A included patients who underwent scaling and root planning (SRP) alone, Group B included patients who underwent SRP and supplemented with vitamin E 200 IU daily at night for 4 weeks. Group C included patients who underwent SRP and supplemented with tablet melatonin 3 mg daily at night for 4 weeks. Estimation of vitamin C was done on day 0, day 30, day 60 and day 90. Results: A total 240 patients were enrolled in the study, 80 in each group. Statistical analysis was done using ‘Z’ test of difference between two sample means for comparison of vitamin C among the three groups. It was observed that, there was a highly significant increase in mean values of vitamin C in group C when compared with group A and group B at 1st, 2nd and 3rd visits (p<0.01). Conclusions: Melatonin acts as an antioxidant in the patients of periodontitis which has positive effect on biochemical parameters of periodontitis, conferring a new facet to the management of periodontitis and an attempt to impede the disease progression.